2010
DOI: 10.1002/jcu.20671
|View full text |Cite
|
Sign up to set email alerts
|

Can contrast‐enhanced sonography distinguish benign from malignant breast masses?

Abstract: The results of our study have not shown any additional benefit in the use of CEUS over conventional triple assessment. The positive trend seen in the higher mean VMS for the malignant tumors needs further investigation with a larger cohort of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 13 publications
(7 reference statements)
0
17
0
2
Order By: Relevance
“…Analyzing the lesions from both qualitative (patterns of enhancement) and quantitative points of view (kinetics patterns) Liu et al On the other hand, Sorelli et al (18) used a dose of 4.8 mL MB in order to evaluate breast tumors in hope to find an additional benefit over the conventional triple assessment when differentiating between benign and malignant neoplasms. This high dose of MB was also applied by Balleyguier et al (19), where they suggested a dose of 5 mL contrast agent in order to detect small vessels, arguing that a half dose was clearly insufficient for studying breast tumors.…”
Section: Discussionmentioning
confidence: 98%
“…Analyzing the lesions from both qualitative (patterns of enhancement) and quantitative points of view (kinetics patterns) Liu et al On the other hand, Sorelli et al (18) used a dose of 4.8 mL MB in order to evaluate breast tumors in hope to find an additional benefit over the conventional triple assessment when differentiating between benign and malignant neoplasms. This high dose of MB was also applied by Balleyguier et al (19), where they suggested a dose of 5 mL contrast agent in order to detect small vessels, arguing that a half dose was clearly insufficient for studying breast tumors.…”
Section: Discussionmentioning
confidence: 98%
“…Scopo Unlike diffusive contrast media (such as those used in magnetic resonance imaging and computed tomography) that enter the extracellular spaces, US contrast agents remain confi ned within the vessels, allowing for clear visualisation of even the smallest vascular structures (the parenchymal microvasculature). US contrast agents have a wide range of applications, especially in studying liver and breast focal lesions and in the fi eld of cardiovascular imaging and haemodynamics [13][14][15]. Few studies have investigated the use of contrast agents in the musculoskeletal system, and no scientifi c contributions to date have studied the use of US contrast agents for studying neurinomas [16].…”
Section: Introductionmentioning
confidence: 98%
“…che si dispongono anche negli spazi extracellulari, il mezzo di contrasto ecografi co rimane confi nato, per le sue caratteristiche fi siche, all'interno dei vasi, consentendo così una precisa visualizzazione anche delle strutture vascolari più piccole (microvascolarizzazione parenchimale). Il MdC ecografi co presenta un ampio campo di applicazione soprattutto in ambito epatico e mammario, per lo studio delle lesioni focali, nel distretto cardio-vascolare e nell'emodinamica [13][14][15]. In letteratura l'impiego del MdC in ambito muscolo-scheletrico è scarsamente rappresentato e non sono stati attualmente riscontrati contributi scientifi ci in merito allo studio dei neurinomi con MdC ecografi co [16].…”
Section: Introductionunclassified
“…In previous studies, ultrasound contrast medium was used to help differentiate between benign and malignant breast disease. However, use of this technique did not always give uniform results [79]. Early breast cancer detection, diagnosis, and treatment have been shown to be the key to improving the cure rate and reducing mortality [10].…”
Section: Introductionmentioning
confidence: 99%